2000
DOI: 10.1007/s002840010122
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis δ-Endotoxin Proteins Show a Correlation in Toxicity and Short Circuit Current Inhibition Against Helicoverpa zea

Abstract: Pesticidal activity of Bacillus thuringiensis delta-endotoxins, Cry1Aa, Cry1Ab, Cry1Ac, and Cry2A, was determined by using the force-feeding bioassay method to 4(th) instar larvae of Helicoverpa zea. H. zea was susceptible to Bt toxins in the order Cry1Ac > Cry1Ab > Cry1Aa > Cry2A with 63.60, 89.04, 159.65, and 375.78 ng/larvae respectively. The abilities of selected Bacillus thuringiensis toxins to inhibit short circuit current (I(SC)) in midgut epithelia of H. zea were also investigated by voltage clamp assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…1). The measured molecular weight (41,485) was within instrumental error (0.05%) of the calculated molecular weight (41,502). Both the whole protein and tryptic digest spectra suggested that the N-terminal methionine residue of the recombinant protein had not been processed.…”
Section: Isolation Of Toxin Gene-xenorhabdus Andsupporting
confidence: 49%
See 1 more Smart Citation
“…1). The measured molecular weight (41,485) was within instrumental error (0.05%) of the calculated molecular weight (41,502). Both the whole protein and tryptic digest spectra suggested that the N-terminal methionine residue of the recombinant protein had not been processed.…”
Section: Isolation Of Toxin Gene-xenorhabdus Andsupporting
confidence: 49%
“…3B). The dose of A24tox required to kill insects (30 -40 ng/g of larvae) is of the same order of magnitude as that of other insecticidal toxins, such as the Tc toxins from Photorhabdus against M. sexta larvae (18), and the insecticidal crystal proteins of B. thuringiensis against Helicoverpa zea (41) and Leptinotarsa decemlineata (42). Injection or ingestion of the Tca complex of P. luminescens strain W14 by M. sexta larvae causes damage to the midgut cells, resulting in a shedding of the midgut epithelium into the gut lumen followed by lysis of the epithelium (43).…”
Section: Discussionmentioning
confidence: 99%
“…Basri (2005) also observed instability in expression of the bar gene in T 1 , T 2 , and T 3 transgenic wheat plants. Karim et al (2000) studied pesticidal activity of Bt endotoxins Cry1Aa, Cry1Ab, Cry1Ac, and Cry2A against fourth instar larvae of Helicoverpa zea and found that H. zea was susceptible to Bt toxins in the order Cry1Ac, Cry1Ab, Cry1Aa, and Cry2A with 63.60, 89.04, 159.65, and 375.78 ng/larvae, respectively. A high concentration of Cry2A protein was needed to achieve complete insect mortality when compared to Cry1A proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The Cry2Aa protein is known to be toxic to prominent lepidopteran insect pests like rice stem borers and brinjal fruit and shoot borer (Maqbool et al 1998, Rao et al 1999. Pesticidal activity of B. thuringiensis δ-endotoxins, Cry1Aa, Cry1Ab, Cry1Ac, and Cry2A against Helicoverpa zea was determined by Karim et al (2000). H. zea was susceptible to Bt toxins in the order Cry1Ac,Cry1Ab,Cry1Aa,and Cry2A with 63.60,89.04,159.65,and 375.78 ng/larvae, respectively.…”
Section: Insect Bioassay Of Cry2ax1 Transgenic Cotton Plantsmentioning
confidence: 99%